S100B Serum Levels in Schizophrenia Are Presumably Related to Visceral Obesity and Insulin Resistance. (10th May 2010) - Steiner, Johann; Myint, Aye Mu; Schiltz, Kolja; Westphal, Sabine; Bernstein, Hans-Gert; Walter, Martin; Schroeter, Matthias L.; Schwarz, Markus J.; Bogerts, Bernhard
Abstract : Elevated blood levels of S100B in schizophrenia have so far been mainly attributed to glial pathology, as S100B is produced by astro- and oligodendroglial cells and is thought to act as a neurotrophic factor with effects on synaptogenesis, dopaminergic and glutamatergic neutrotransmission. However, adipocytes are another important source of S100B since the concentration of S100B in adipose tissue is as high as in nervous tissue. Insulin is downregulating S100B in adipocytes, astrocyte cultures and rat brain. As reviewed in this paper, our recent studies suggest that overweight, visceral obesity, and peripheral/cerebral insulin resistance may be pivotal for at least part of the elevated S100B serum levels in schizophrenia. In the context of this recently identified framework of metabolic disturbances accompanying S100B elevation in schizophrenia, it rather has to be attributed to systemic alterations in glucose metabolism than to be considered a surrogate marker for astrocyte-specific pathologies.